NOȚIUNEA DE RĂSPUNDERE PARLAMENTARĂ: CONȚINUT ȘI ACCEPȚIUNI - MICU, Victor (SUPREMANCE OF LAW, 2016)
Article contains a comparative analysis of the opinions expressed in contemporary legal doctrine to determine the content and meanings recognized of notion of parliamentary accountability (responsibility). In conclusion, it stated that parliamentary responsibility is an institution of parliamentary law which means responsibility of parliament and parliamentarians liability for breach of various rules of law; it is a similar institution of „ministerial responsibility”.
Keywords: responsibility; parliamentary responsibility; responsibility of parliament; deputy liability